STRUCTURAL AND OPTICAL CHARACTERIZATION OF VACUUM EVAPORATED ZINC SELENIDE THIN FILMS - Andalipa Islam; Chitra Das; Shamima Choudhury; Mehnaz Sharmin; Tahmina Begum (European Scientific Journal, ESJ, 2014)
Optical and structural characterization of Zinc Selenide (ZnSe) thin films (thickness ranging between 200 - 500 nm) prepared by vacuum (~10-6 Torr) evaporation method were investigated. The thin films were deposited with varying substrate temperature in the range 373 - 573K. Optical measurements were carried out with UV-VIS-NIR spectrophotometer with photon wavelength ranging between 300-2500 nm. The absorption coefficient, energy band gap, refractive index and extinction coefficient were determined using transmission and reflection spectra at the same wavelength range. The dependence of absorption coefficient in the photon energy had been determined. Analysis showed that direct transition occured with band gap energies ranges from 2.6 eV to 2.9 eV. Refractive indices and extinction coefficients were evaluated in the above spectral range. For structural properties, 300nm films were deposited with varying substrate temperatures and were vacuum annealed in situ at 373 K for one hour. The X- ray diffraction (XRD) patterns showed polycrystalline nature of films having cubic (Zinc blende) structure. The most preferential orientation is along [111] direction for all deposited films together with other abundant planes [220] and [311]. Structural parameters such as lattice constant, grain size, internal stress, microstrain, dislocation density were calculated. The value of lattice constant was estimated to be5.660 Å to 5.761 Å.. The grain sizes were calculated to be which ranges between 266 Å to 384 Å. With the increase of substrate temperature the average grain size of the ZnSe films increases, as revealed from the XRD studies.